Protective Effect and Mechanism of Bone Morphogenetic Protein-4 on Apoptosis of Human Lens Epithelium Cells under Oxidative Stress. (29th January 2021) - Du, Bei; Zheng, Jia-Lin; Huang, Liang-Yu; Zhang, Hong; Wang, Qiong; Hong, Ya-Ru; Zhang, Xiao-min; Li, Xiao-Rong; Dong, Li-Jie
Abstract : Bone morphogenetic proteins (BMPs), a member of the transforming growth factor β (TGF- β ) superfamily, are abundant in human ocular tissues and play an important role in lens development. Targeted deletion of BMP-4 in mice results in failure of lens placode formation. Following lens maturation, the formation of senile cataracts is demonstrably associated with free radical-related oxidative stress. Previous studies reported that BMPs play an antiapoptotic role in cells under oxidative stress, and the BMP-4 signal is important in inflammation regulation and homeostasis. BMP-4 evidently suppressed the apoptosis of human lens epithelial cells (HLECS) under oxidative stress induced by H2 O2 . This protective antiapoptotic effect is partly due to a decrease in caspase-3 activity and reactive oxygen species (ROS) level. Furthermore, the expression of activating transcription factor- (ATF-) 6 and Krüppel-like factor- (KLF-) 6 increased under oxidative stress and decreased after BMP-4 treatment.